2010
DOI: 10.1167/iovs.09-4559
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Assessment of Schlemm's Canal by Spectral-Domain Optical Coherence Tomography

Abstract: Aqueous outflow structures, including SC and CCs, can be noninvasively assessed in the human eye. These measurements will be useful in physiological studies of AO and will be clinically useful in the determination of the impact of glaucoma therapies on IOP as well as presurgical planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
178
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(190 citation statements)
references
References 10 publications
(9 reference statements)
7
178
0
1
Order By: Relevance
“…Kagemann et al [5] investigated SC using Spectral-domain OCT and found that, in glaucoma patients, SC was smaller than in the controls. They also found that SC was significantly larger on the nasal side than on the temporal one.…”
Section: Sc Dimension Was Investigated By Ultrasound (80-mhz Andmentioning
confidence: 99%
“…Kagemann et al [5] investigated SC using Spectral-domain OCT and found that, in glaucoma patients, SC was smaller than in the controls. They also found that SC was significantly larger on the nasal side than on the temporal one.…”
Section: Sc Dimension Was Investigated By Ultrasound (80-mhz Andmentioning
confidence: 99%
“…It is the final barrier for the AH before returning to systemic circulation, but its specific contribution to AH outflow resistance is unknown (4). Interestingly, glaucoma patients have a smaller SC (9), and agenesis or hypoplasia of the SC has been implicated in primary congenital glaucomas (10)(11)(12)(13). However, it is still unknown whether the SC is a component of the blood or the lymphatic vascular system (1,4,14).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to observe alterations in resistance to SC collapse induced by perturbations of smooth muscle has been shown in an animal model 18 . We have demonstrated the ability to non-invasively image the primary aqueous humor outflow system in living human eyes distal to and including SC using spectral domain optical coherence tomography (OCT) [19][20][21] . Using this technique, we have demonstrated the ability to quantify the morphometric response of the TM and SC to acute IOP elevation 22 .…”
Section: Introductionmentioning
confidence: 99%